Sistema para el control administrativo de la Hacienda agrícola bananera María del Carmen del cantón La Maná - Cedeño Cedeño, Francisco Adrián (2012)
The investigative work present consists in the elaboration of a System for the Administrative control in the Hacienda Banana Agricultural María del Carmen on the La Maná Canton, it will be an efficient tool to log, track and structure information of banana agricultural processes that are generated in the same allowing the optimization of resources to the administrators. It will also offer security in the storage and prosecution of the information, counting with necessary tools for the backup and restore of the database The administrative system has been developed using the following tools: • Visual Microsoft Studio.Net 2010. • Sql Server Management Studio 2008. The spiral method is used that software development guided objects; this technology has been the fundamental pillar for developing each one of the stages of those that it is compound the software. To establish this construction model one carries out a comparison among the different models of software development, being adjusted to the necessity before the pattern mentioned because this it is managed by cycles, being possible to add improvements and new requirements without breaking up with the methodology, due to the flexibility of this cycle of software life. In the summary, this system will allow to administer banana agricultural processes (spraying, cultivation, cutting, packing, loading and transportation of bananas) that are performed in each of the farms belonging to the Hacienda in an easy and fast, changing the traditional method (manual) to automatic.